Three dimensionally ordered mesoporous hydroxylated NixCo3−xO4 spinels for the oxygen evolution reaction: on the hydroxyl-induced surface restructuring effect. Issue 15 (3rd April 2017) - Abidat, I.; Morais, C.; Comminges, C.; Canaff, C.; Rousseau, J.; Guignard, N.; Napporn, T. W.; Habrioux, A.; Kokoh, K. B.
Abstract : Mesoporous nickel cobaltites synthesized using a nanocasting technique show high OER activity after surface modifications induced by potential cycling. Abstract : Surface restructuration upon potential cycling of three dimensionally ordered Ni x Co3− x O4 spinels for the oxygen evolution reaction (OER) in an alkaline medium is studied using structural, spectroscopic and electrochemical techniques. It was shown that the intrinsic activity of different catalysts depends on the incorporated amount of nickel and surprisingly correlates with the Co III /Co IV peak potential. The electrochemical activity of the OER is amazingly improved upon potential cycling. It was observed that potential cycling induces an increase of active sites up to 45% on the most effective electrocatalyst. This unexpected increase in activity is very pronounced and becomes stable after 30 voltammetric cycles. Such a phenomenon is explained by the formation of a layered mixed nickel/cobalt oxyhydroxide active site whose oxidation potential is related to the nickel amount in the catalyst. The formation of this layer is promoted by the surface hydroxylation degree of non-cycled catalysts. In these catalysts, nickel modulates the electronic properties of the active site, which modifies the adsorption energies of key oxygenated intermediates. The synthesis route proposed herein allows an efficient way for obtaining high specific surface areas as well as highly hydroxylated surfaces, the latter being the key factor in the enhancement of the electrocatalytic activity of nickel cobaltites.